Model-based design for effective control system development - Wu, Wei (Mechanical engineer) (Information Science Reference, 2017)
"[This book] is a critical source of scholarly information on model-centric approaches and implementations for control and other similar dynamic systems. Highlighting innovative topics such as configuration management, controllability analysis, and modeling requirements, this book is ideally designed for engineers, researchers, academics, project managers, and professionals interested in the design of embedded control systems"- Resumé vydavatel
Keywords: automatické řízení; řídicí systémy; matematické modely; automatic control; mathematical models; control systems; monografie; elektronické knihy; monographs; electronic books